COMPARING THE EPICA AND VOSTOK DUST RECORDS DURING THE LAST 220,000 YEARS: STRATIGRAPHICAL CORRELATION AND PROVENANCE IN GLACIAL PERIODS - Delmonte B.; Petit J.-R.; Maggi V.; Basile-Doelsch I.; Michard A.; Revel-Rolland M.; Jagoutz E.; Grousset F. (My University, 2004)
A new aeolian dust record from the first 2200 m of the EPICA-Dome C ice core (75°06′S, 123°21′E) covering about 220,000 years of climatic history is compared to the Vostok (78°28′S, 106°48′E) ice core [Nature 399 (1999) 429]. The two dust profiles are very similar and several common dust events allow to establish stratigraphical links.The late Quaternary period is characterized at both sites, and likely overall East Antarctic plateau, by high dust input during glacial periods. In the EPICA-Dome C ice core, the dust flux rises by a factor of ∼25, ∼20 and ∼12 in glacial stages 2, 4 and 6 with respect to interglacial periods (Holocene and stage 5.5). The magnitude and pattern of changes are comparable in the Vostok ice core.In this study, the geographical origin of ice core dust (ICD) in cold periods has been investigated at both sites through 87Sr/86Sr versus 143Nd/144Nd isotopic tracers, following the previous studies of Grousset et al. [Earth Planet. Sci. Lett. 111 (1992) 175] and Basile et al. [Earth Planet. Sci. Lett. 146 (1997) 573].The new data and the existing ones allow to define the isotopic fields for dust at the two Antarctic sites that are almost identical and restricted into the 0.708<87Sr/86Sr<0.711 and −5<εNd(0)<+5 ranges. This suggests a common geographical provenance for dust at Vostok and Dome C and for all the glacial periods of the late Pleistocene.To decipher the ICD provenance, more than 50 samples of loess and aeolian deposits, sands and fluvioglacial sediments from the Potential Source Areas (PSAs) of the Southern Hemisphere have been collected. However, the methodology has been refined with respect to former studies. First, the isotopic fractionation that can occur in function of grain size has been taken into account, and the PSA's signature has been defined in the <5 μm size range, within which fine-grained dust reaching Antarctica is found. Moreover, a possible contribution from carbonates on the samples from PSAs has also been also considered.South Africa and Australia can be excluded as dominant sources, but a partial overlap arises among southern South America, New Zealand and the Antarctic Dry Valleys isotopic fields, these latter two documented for the first time.A possible contribution from all these three sources cannot be excluded, but complementary arguments suggest the dominant contribution to East Antarctic dust in glacial times deriving from the southern South American region of Patagonia and the Pampas.This study shows a first-order uniformity in the dust flux and geographical provenance to the East Antarctica plateau during glacial periods.
Keywords: Dust; Ice cores; Antarctica; Sr–Nd; Paleoclimate